Lizzie Borden on Trial : Murder, Ethnicity, and Gender - Conforti, Joseph A. (Book collections on Project MUSE., 2015)
"This is a retelling of the famous story of Lizzie Borden, charged with killing her father and stepmother with "forty whacks" of a hatchet. Conforti describes the crime, the investigation, and the trial that resulted in her acquittal. He places the trial in the context of the social and cultural climate of late 19th century Fall River, a town made rich by textile factories, most of which were owned by one branch or another of the Bordens', but that was increasingly the home of immigrants, brought in to work on the mills, and now challenging the domination of Fall River by wealthy Yankees like the Bordens. Also, he shows that the Borden case illustrates the way unmarried women like Lizzie Borden were treated. Conforti believes that Lizzie did it but the book is not really about her guilt or innocence but how the case illustrates the position of a woman like Lizzie in society and how that tipped the balance toward her acquittal"--